2020
DOI: 10.3389/fvets.2020.00317
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition and Regulatory Gene Expression in Late-Term Embryos of ACRB and COBB Broilers

Abstract: Cobb broilers (COBB) have been heavily selected for their production performance in the past several decades, while the Athens Canadian Random Bred (ACRB) chickens, a meat-type breed, have been kept as a non-selected control strain. The purpose of this study was to compare these two lines of chickens at late embryonic development and identify the molecular markers and fatty acid profiles underlining their differences in growth performance due to selection. Fertilized eggs of the ACRB (n = 6) and COBB (n = 6) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Parallel changes in FA composition were found between the liver and serum in the current study. As the incubation proceeded, hepatic and serum UFA increased and SFA decreased, which was consistent with the FA changes reported in chicken and turkey embryos ( Ding and Lilburn, 1996 ; Su et al., 2020 ). In contrast to the FA composition of the liver or serum, that of the yolk sac stayed constant throughout embryogenesis, especially distinguished by a steady level of PUFA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Parallel changes in FA composition were found between the liver and serum in the current study. As the incubation proceeded, hepatic and serum UFA increased and SFA decreased, which was consistent with the FA changes reported in chicken and turkey embryos ( Ding and Lilburn, 1996 ; Su et al., 2020 ). In contrast to the FA composition of the liver or serum, that of the yolk sac stayed constant throughout embryogenesis, especially distinguished by a steady level of PUFA.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the egg yolk is the sole source of n-6 and n-3 polyunsaturated FA (PUFA) in the chick embryo due to the absence of desaturases that insert double bonds beyond the δ-9 carbon ( Cherian, 2015 ). Oleic acid (OA) is the most abundant FA in the yolk of developing chick embryos, which is key for energy supply during incubation ( Şahan et al., 2014 ; Su et al., 2020 ). We hypothesized that IOF-OA could achieve a beneficial effect on embryonic development by altering FA profile and lipid metabolism and modifying the regulation of transcription of different genes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the methods described as previous experiment ( Su et al., 2020 ). After grinding, 0.5 g liver sample was used to mix with 0.5 mL 0.5 g/l internal standard undecylenic acid methyl ester (Sigma), 2 mL 95% ethanol, 2 mL pure water and 0.1 g pyrogallic acid in a 50-mL screw-thread erlenmeyer flask, and then 10 mL HCL (8.3 mol/l) were added using water bath heating hydrolyzed the liver sample (80°C, 40 min).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that during adipocyte formation (in utero and early infancy), exposure of animals to excessive n−6 fatty acids may promote fat deposition early in life ( Gibson et al, 2011 ). The n−6 to n−3 PUFA ratio is also associated with obesity in animals ( Su et al, 2020 ). In addition, many studies have shown that obesity and obesity-related diseases such as nonalcoholic fatty liver disease ( NAFLD ) are closely associated with a decrease in the biodiversity of intestinal microflora ( Arslan, 2014 ; Panasevich et al, 2016 ), and this association is also present in this study, that is, a reduction in the ɑ-biodiversity of intestinal microflora due to supplemented cholamine was associated with an increase in liver fat.…”
Section: Discussionmentioning
confidence: 99%